2016
DOI: 10.1039/c5ra27554g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of malathion on mesoporous monetite obtained by mechanochemical treatment of brushite

Abstract: Synthesis of mesoporous monetite by mechanochemical treatment brushite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…The peaks at ∽32° and 40° increase in intensity, while at ∽34°, the intensity of the peaks directly related to the presence of Ni, Co, and Cu ions decreases. While at 26, 29, and 53°, new peaks appear in the doped brushite samples, which also caused a decrease in the network parameter of 4.99 nm, a value lower than the 5.77 nm obtained for nDCPD, without doping, together with the particle size from 9.26 to 4.45, 4.08, and 4.35 Å, for Ni, Co, and Cu, respectively, which was determined with the Scherrer Equation [39,40]. This may be due to the fact that the Ca ions of nDCPD without doping (1.12 Å) are replaced during the adsorption process by the ions of Ni (0.78 Å), Co (0.63 Å), and Cu (0.69 Å), which implies that part of the ions are retained inside the structure of nDCPD [40].…”
Section: Kinetic Studymentioning
confidence: 71%
See 1 more Smart Citation
“…The peaks at ∽32° and 40° increase in intensity, while at ∽34°, the intensity of the peaks directly related to the presence of Ni, Co, and Cu ions decreases. While at 26, 29, and 53°, new peaks appear in the doped brushite samples, which also caused a decrease in the network parameter of 4.99 nm, a value lower than the 5.77 nm obtained for nDCPD, without doping, together with the particle size from 9.26 to 4.45, 4.08, and 4.35 Å, for Ni, Co, and Cu, respectively, which was determined with the Scherrer Equation [39,40]. This may be due to the fact that the Ca ions of nDCPD without doping (1.12 Å) are replaced during the adsorption process by the ions of Ni (0.78 Å), Co (0.63 Å), and Cu (0.69 Å), which implies that part of the ions are retained inside the structure of nDCPD [40].…”
Section: Kinetic Studymentioning
confidence: 71%
“…Similarly, it can be noticed that the models that do not adequately describe the process of metal removal in nDCPD are those that are related to the mass transfer both external and internal, independent of the temperature, the concentration of the adsorbent material, and the presence of another metal ion in the same solution; so it can be inferred that the removal process of these metals does not present problems of mass transfer. Figure 12 shows the SEM image of the nDCPD doped with the Ni, Co, and Cu ions, where the main characteristics of nDCPD (Figure 12a), monoclinic disk morphology [1,15,29,39], which does not present significant changes in the presence of Ni (Figure 12b), Co (Figure 12c), and Cu (Figure 12d) ions can be observed, probably because the vast majority of metal ions are adsorbed on the surface of nDCPD. The XRD patterns of nDCPD doped with Ni, Co, and Cu are shown in Figure 13, and according to the International Center of Diffraction Data Chart (JCPDS) database, some changes are observed in the samples with metal ions compared to that of nDCPD without doping [1].…”
Section: Kinetic Studymentioning
confidence: 99%
“…Habila et al [18] report the malathion adsorption by activated carbon derived from a copyrolysis process of agricultural and municipal solid wastes, such as paper, plants, and plastics. Mirković et al [19] report the use of mesoporous monetite as efficient adsorbent of malathion from aqueous solutions. Harper Jr. et al [20] demonstrated the feasibility of use of metallic materials such as iron and copper for malathion adsorption, but the adsorption capacity was low compared to the typical adsorbent materials used (activated carbon).…”
Section: Introductionmentioning
confidence: 99%
“…Several two and three-dimensional structures have been isolated and different synthesis strategies have been proposed. Among them, Dibasic Calcium Phosphate Anhydrous (DCPA) (CaHPO 4 , Monetite) and Dibasic Calcium Phosphate Dihydrate (DCPD) (CaHPO 4 •2H 2 O, Brushite) with molar ratio Ca/P=1 have gained much attention owing to their wide applications such as potential precursors for the synthesis of biomaterials useful for the orthopedic engineering and dental implants [4,5], selective adsorbents of pesticides, organic pollutants and containment matrices of radioactive elements in environmental science [6,7] and supports of active phases in numerous heterogeneous catalytic reactions, among others vapour-gas conversion of alcohols [8], oxidative dehydrogenation of alkanes [9] and hydroxylation of aromatic compounds [10].…”
Section: Introductionmentioning
confidence: 99%